The effect of SAQ trainings in developing some anaerobic abilities and basic skills of table tennis players - Ihsandin Othman Abdulla (دراسات وبحوث التربية الرياضية, 2025)
The physical abilities of table tennis players are crucial in determining their success in the sport. In order to develop those physical aspects and abilities modern training methods should be applied, such as speed, agility and quickness (SAQ) method, this type of training method enhances anaerobic capabilities. The study aims to prepare specific training program using SAQ method to develop some anaerobic abilities as well as some basic skills of table tennis players. 6 male players of Brayate sport club selected as study population and sample. The experiment design of one independent sample used in the study. The duration of SAQ training program lasted for 6 weeks within 3 training units per week. The findings of the study show that SAQ training is an effective method of training to develop physical components, in addition, the results show an improvement in the game basic skills. Physical fitness significantly impacts table tennis performance through the development of agility, speed and strength